Knowledge management - A driving force in exploiting big data to enhance organizational performance: An overview - Nadia, Al-Muqrashi; Muhammad, Saqib (UUM College of Business, 2016)
Knowledge is considered to be a strategic imperative of all the organizations to sustain, compete and excel in this competitive world. Today it is considered to be more powerful and valuable asset of organizations, though in a nascent but rapidly growing practice that is helping organizations to gain insights of their businesses.The increasing size of artifacts and business processes has resulted into emergence of Big Data.The quality, dynamic variation and diverse nature of information, challenges any organization to possess higher performance; hence, Knowledge management holds a very important role in managing multifaceted information and association to organizational performance improvement.The current literature focuses on the issues related to Knowledge Management of Big Data; structured and unstructured, and challenges faced by enterprises in performance improvement.The study will address the need identified and will focus on some of the Knowledge Management concerns in terms of organizational performance.Also this study is based on the concepts related to the idea that big data is actually big knowledge and knowledge management is valuable asset of organizations to enhance their performance.